Incidence of HIV infection and associated factors among men who have sex with men in Zhejiang, China: a cohort study - Wang, Hui; Zhou, Wenkai; Pan, Xiaohong; Ma, Qiaoqin; Chen, Lin; Zhou, Xin; Jiang, Tingting; Chen, Wanjun (Frontiers in Public Health, 2025)
AimMen who have sex with men (MSM) contribute increasingly to the burden of HIV infection due to their high-risk sexual behaviors; however, studies focusing on the sexual behaviors among student MSM population remain limited. This study aims to investigate the incidence of HIV infection among MSM, while exploring high-risk sexual behavior in student MSM in Zhejiang province, China.MethodProspective cohort study was conducted among MSM population in four cities in Zhejiang province. Information including socio-demographic characteristics as well as sexual behaviors were collected at baseline. Follow-up surveys and testing for HIV infection were conducted every 3 months. Univariable and multivariable logistic regression were performed to assess risk factors for HIV infection, investigate the sexual behavior differences between student and non-student MSM groups. Cox regression analyses were employed to discover potential association among various risk factors.Result2081 HIV-negative MSM were enrolled in our cohort and 36 participants were infected with HIV. The incidence density of HIV infection was 2.15 per 100 person-years among this population. Student MSM are more likely to take sexual role of versatile (OR: 1.56, 95% CI: 1.05–2.32, p = 0.029) and receptive only (OR: 2.65, 95% CI: 1.62–4.08, p < 0.001) during anal intercourse, with a lower rate of previous HIV testing (OR: 0.45, 95% CI: 0.31–0.66, p < 0.001). Cox regression discovered that MSM who had more than 6 partners in anal sexual intercourse were more likely to obtain HIV-seroconversion than who had one fixed partner (HR: 5.14, 95% CI: 1.67–10.59, p < 0.001), participants who sometimes use condoms (HR: 4.11, 95% CI: 1.28–13.16, p = 0.017) and never use condoms (HR: 2.57, 95% CI: 1.16–5.66, p = 0.020) were more vulnerable to be infected by HIV compared to those use condoms constantly. Versatile (HR: 5.30, 95% CI: 1.65–17.06, p = 0.005) and receptive only role (HR: 3.23, 95% CI: 1.05–9.96, p = 0.042) in anal intercourse were more likely to be infected by HIV than insertive only.ConclusionHigh-risk behaviors, particularly inconsistent condom uses during anal sex, significantly increase the risk of HIV infection. Student MSM exhibited persistent high-risk behaviors and low HIV testing rates. Greater attention and tailored interventions are needed to promote safer sexual practices and reduce HIV transmission in this population.